2018
DOI: 10.1073/pnas.1718356115
|View full text |Cite
|
Sign up to set email alerts
|

Amide-forming chemical ligation via O -acyl hydroxamic acids

Abstract: The facile rearrangement of "-acyl isopeptides" to native peptide bonds via ,-acyl shift is central to the success of native chemical ligation, the widely used approach for protein total synthesis. Proximity-driven amide bond formation via acyl transfer reactions in other contexts has proven generally less effective. Here, we show that under neutral aqueous conditions, "-acyl isopeptides" derived from hydroxy-asparagine [aspartic acid-β-hydroxamic acid; Asp(β-HA)] rearrange to form native peptide bonds via an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 58 publications
1
15
0
Order By: Relevance
“…For comparison studies, Asp‐RTD1 18 was obtained by oxidation of Asn(OH)‐RTD1 17 with NaIO 4 [14] (1 equiv) in 20 mM PBS (pH 7.2) at 0 °C, which quickly converted Asn(OH) to Asp in 5–10 min. Previously, Pentelute and co‐workers showed that NaNO 2 oxidation can also be used to convert Asn(OH) to Asp [9c] . Asn‐RTD1 19 was prepared in the same manner as Asn(OH)‐RTD1 17 by cyclization at the Asn residue using butelase‐1.…”
Section: Figurementioning
confidence: 99%
“…For comparison studies, Asp‐RTD1 18 was obtained by oxidation of Asn(OH)‐RTD1 17 with NaIO 4 [14] (1 equiv) in 20 mM PBS (pH 7.2) at 0 °C, which quickly converted Asn(OH) to Asp in 5–10 min. Previously, Pentelute and co‐workers showed that NaNO 2 oxidation can also be used to convert Asn(OH) to Asp [9c] . Asn‐RTD1 19 was prepared in the same manner as Asn(OH)‐RTD1 17 by cyclization at the Asn residue using butelase‐1.…”
Section: Figurementioning
confidence: 99%
“…In this case, the formation of side products resulting from the internal cyclization of the peptides, such as aspartimide‐ or β‐Asp‐containing peptides, would be assumed to be more likely than that in the case of Glu(Dbz)‐containing peptides. In general, the synthesis of the desired Asp/Asn‐based peptides is expected to be more challenging than that of the synthesis of their Glu/Gln‐based counterparts, because aspartimide contains a five‐membered ring structure. Fortunately, under the same conditions as those used for the synthesis of Glu/Gln‐containing peptides, the Asp/Asn‐containing peptides were obtained without significant amounts of side products, such as aspartimide/β‐Asp(Asn)/D‐Asp(Asn), respectively (Figure and the Supporting Information).…”
Section: Figurementioning
confidence: 99%
“…In 2018, the group of Pentelute reported O ‐acyl‐Asn isopeptide mediated ligation. The ester bond was constructed on the side chain of hydroxyl‐Asn (aspartic acid–β‐hydroxamic acid) by capturing the peptide thioester with the hydroxamic acid . Subsequent O‐to‐N acyl transfer mediated by a seven‐membered cyclic intermediate produced a peptide bond.…”
Section: Application Of Isoacyl Structural Motifs In Synthetic Peptidmentioning
confidence: 99%
“…The ester bond was constructed on the side chain of hydroxyl-Asn (aspartic acid-b-hydroxamica cid) by capturing the peptidet hioester with the hydroxamic acid. [54] Subsequent O-to-N acyl transfer mediated by as evenmembered cyclic intermediate produced ap eptideb ond. The hydroxyl-Asn residue of the ligatedp roduct could be reduced to asparagine by zinc/ascorbic acid or oxidized by sodium nitrite to aspartica cid,t hus realizing at raceless ligation (Scheme 3F).…”
Section: Application Of Isoacyl Motifs In Peptide Ligationmentioning
confidence: 99%